Comparison of simple screening tests for fat malabsorption. Issue 6275 (9th May 1981) - West, P S; Levin, G E; Griffin, G E; Maxwell, J D
Abstract : Three tests were evaluated as screening procedures for fat malabsorption--namely, measurement of serum optical density, serum triglyceride concentration, and 14CO2 breath excretion after the administration of a 60 g fat meal containing 10 muCi glycerol tri[1-14C]oleate. The results of these tests were compared with fat excreted in a three-day faecal collection after adjustment for completeness of collection as assessed by using non-absorbable radio-opaque markers. Fifty-two patients with various symptoms and eight normal subjects were studied. The maximum increase in serum optical density or triglyceride concentration above the fasting value discriminated poorly between subjects with normal and increased adjusted faecal fat excretion. In contrast, seven- or eight-hour cumulative 14CO2 breath excretion provided good discrimination with only four (7%) false-positive and no false-negative results. The simplicity and convenience of breath analysis make it an attractive alternative to analysis of faecal fat excretion in screening for fat malabsorption.